2006
DOI: 10.1093/jn/136.6.1498
|View full text |Cite
|
Sign up to set email alerts
|

The Elevation of Ingested Lipids within Plasma Chylomicrons Is Prolonged in Men Compared with Women

Abstract: The lipemic response to a high-fat meal is greater in men than in women. However, sex-related differences in the metabolic fate of ingested fat are not well understood. The purpose of this study was to measure the recovery of ingested fat in plasma fractions of chylomicrons (CHYLO), VLDL, and plasma fatty acids, as well as in expired breath (i.e., oxidation) in men and women. Nonobese subjects (n = 10; 5 men, 5 women) consumed 0.7 g fat/kg body weight containing 7 mg/kg of [1,1,1-13C]-trioleate the morning aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
2
28
2
Order By: Relevance
“…Women had lower chylomicron-TG levels and lower 18 F activity in chylomicron-TG postprandially when compared with men in both IGT 2 and IGT + groups, consistent with findings by others that could be explained by faster chylomicron-TG clearance in women (26). In rats, testosterone reduces chylomicron clearance and postheparin LPL activity (27).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Women had lower chylomicron-TG levels and lower 18 F activity in chylomicron-TG postprandially when compared with men in both IGT 2 and IGT + groups, consistent with findings by others that could be explained by faster chylomicron-TG clearance in women (26). In rats, testosterone reduces chylomicron clearance and postheparin LPL activity (27).…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that VLDL-TG secretion from DFAs may have been increased in women in the current study. However, no sex difference in DFA incorporation into VLDL-TG was observed in a previous report using 14 C-labeled oleate tracer (26).…”
Section: Discussioncontrasting
confidence: 58%
“…Previous work has found that the plasma TG response after a meal is often greater in men than in women (Couillard et al 1999;Horton et al 2002;Koutsari et al 2004;Sopowski et al 2001), and this sex-specific difference in lipemic response to a fat meal may contribute to the delayed development of CVD in women compared with men (Rosamond et al 2007). More specifically, we recently demonstrated that alterations in chylomicron metabolism (i.e., prolongation of chylomicrons in men compared with women), explained much of the sex-related difference in post-prandial lipemia after a fat meal (Knuth and Horowitz 2006). Because chylomicrons and chylomicron remnants are known to have potent atherogenic properties (Sakurai et al 2005;Yu et al 2000;Zilversmit 1979), persistent elevation in these factors may help explain the sex-related differences in cardiovascular health.…”
Section: Introductionmentioning
confidence: 92%
“…Exercise seems to be more efficacious in lowering PPL for women than for men (34). This may be attributed to lower baseline concentrations of VLDLs in women than in men and a slower rate of chylomicron 14 clearance in men (55,57). However, when differences in baseline TG are controlled for, there does not seem to be a sex difference with regard to PPL (34).…”
Section: Exercise and Lipid Metabolismmentioning
confidence: 99%